2001
DOI: 10.1557/proc-692-h4.4.1
|View full text |Cite
|
Sign up to set email alerts
|

PbTe Flash Evaporation on Si <100> Substrates for Heterojunction Infrared Detectors

Abstract: This work is to present results of flash evaporation of PbTe directly over single crystals p-type Si substrates, in order to produce heterojunction infrared detectors (HIRD), working at 4.3.tm IR wavelength. The evaporation was performed on modified JEOL vacuum equipment, model JEE4B(a), working with vacuum pressure around 10-5 torr, using diffusion pump. The HIRDs produced with this method presented the same detectivity (D*) values of HIRDs made with Hot Wall Epitaxial System (HWE)(b), in which PbTe epitaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sahay and Guruswamy 22 substrates. Guimaraẽs et al 23 used molecular beam epitaxy and flash evaporation to epitaxy PbTe materials on Si substrates to form heterostructure detectors, and the detectivity of the detectors prepared by the two methods was 6.7 × 10 6 cm Hz 1/2 W −1 and 4.8 × 10 5 cm Hz 1/2 W −1 under laser irradiation at 4.3 μm, respectively. In summary, some studies have confirmed the feasibility of heterogeneous growth of high-quality lead telluride materials on a silicon surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahay and Guruswamy 22 substrates. Guimaraẽs et al 23 used molecular beam epitaxy and flash evaporation to epitaxy PbTe materials on Si substrates to form heterostructure detectors, and the detectivity of the detectors prepared by the two methods was 6.7 × 10 6 cm Hz 1/2 W −1 and 4.8 × 10 5 cm Hz 1/2 W −1 under laser irradiation at 4.3 μm, respectively. In summary, some studies have confirmed the feasibility of heterogeneous growth of high-quality lead telluride materials on a silicon surface.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the approximate lattice spacing in the (200) PbTe and (111) Si directions, PbTe films can be epitaxially grown on (111) Si substrates. Guimarães et al used molecular beam epitaxy and flash evaporation to epitaxy PbTe materials on Si substrates to form heterostructure detectors, and the detectivity of the detectors prepared by the two methods was 6.7 × 10 6 cm Hz 1/2 W –1 and 4.8 × 10 5 cm Hz 1/2 W –1 under laser irradiation at 4.3 μm, respectively.…”
Section: Introductionmentioning
confidence: 99%